USP47 deubiquitylates Groucho/TLE to promote Wnt-β-catenin signaling - Kassel, Sara; Hanson, Alison J.; Benchabane, Hassina; Saito-Diaz, Kenyi; Cabel, Carly R.; Goldsmith, Lily; Taha, Muhammad; Kanuganti, Aksheta; Ng, Victoria H.; Xu, George; Ye, Fei; Picker, Julia; et al. (Science signaling, 2023)
The Wnt-β-catenin signal transduction pathway is essential for embryonic development and adult tissue homeostasis. Wnt signaling converts TCF from a transcriptional repressor to an activator in a process facilitated by the E3 ligase XIAP. XIAP-mediated monoubiquitylation of the transcriptional corepressor Groucho (also known as TLE) decreases its affinity for TCF, thereby allowing the transcriptional coactivator β-catenin to displace it on TCF. Through a genome-scale screen in cultured Drosophila melanogaster cells, we identified the deubiquitylase USP47 as a positive regulator of Wnt signaling. We found that USP47 was required for Wnt signaling during Drosophila and Xenopus laevis development, as well as in human cells, indicating evolutionary conservation. In human cells, knockdown of USP47 inhibited Wnt reporter activity, and USP47 acted downstream of the β-catenin destruction complex. USP47 interacted with TLE3 and XIAP but did not alter their amounts; however, knockdown of USP47 enhanced XIAP-mediated ubiquitylation of TLE3. USP47 inhibited ubiquitylation of TLE3 by XIAP in vitro in a dose-dependent manner, suggesting that USP47 is the deubiquitylase that counteracts the E3 ligase activity of XIAP on TLE. Our data suggest a mechanism by which regulated ubiquitylation and deubiquitylation of TLE enhance the ability of β-catenin to cycle on and off TCF, thereby helping to ensure that the expression of Wnt target genes continues only as long as the upstream signal is present.
Gesehen am 31.03.2023